Transport and Fluctuations in the Quantum Dot Heat Engine - Wu,Jiayang (2025)
Quantum effects at the nanoscale offer significant potential for future device technologies. A quantum dot heat engine, for instance, is able to convert heat into electrical current. This thesis investigates the transport properties and current fluctuations in a single-level quantum dot heat engine operating in the sequential tunneling regime. Based on the existing experimental data, both the current and its noise characteristics are analyzed and interpreted. Electron transport is modelled with rate equations, and analytical expressions for the fluctuations are derived with full counting statistics. Theoretical models are fitted to experimental thermocurrent measurements to extract key parameters such as tunneling rates and reservoir temperatures. However, a difference is observed between measured and calculated current noise, with a factor of approximately 100. Further analysis attributes this deviation to the energy-level fluctuations induced by gate voltage instability, evidenced by 1/f-like noise in the power spectral density. These findings reveal that, in the experiment, gate voltage fluctuations dominate the overall noise characteristics, while the contribution from intrinsic electron transport is comparatively minor. The methods and models developed provide a framework for analyzing similar nanoscale heat engine systems and contribute to the broader understanding of fluctuation phenomena in nanoscale thermoelectric devices.